Hybrid passivity‐based control of a three single‐phase star‐connected unidirectional five‐level rectifier with a space vector pulse‐width modulation algorithm for voltage balance - Cheng, Hong; Yang, Daokuan; Wang, Cong; Wang, Ning; Tian, Changgeng (International journal of circuit theory and applications, 2024)
Summary The unidirectional multilevel rectifier has been used in numerous industrial applications due to its reduced active power switches, higher power density, and lower cost compared to conventional bidirectional converters. Recently, the unidirectional five‐level rectifier has been proposed for its lower device stress and the potential for extension to higher levels. However, it adopts a conventional linear proportional integral (PI) control strategy and sinusoidal pulse‐width modulation (SPWM) method, resulting in a complex control structure, particularly for the balance control of the midpoint voltage, and suboptimal dynamic performance. To address this issue and enhance system's large‐scale stability, a hybrid passivity‐based control (PBC) strategy, along with a simplified mathematical model, has been proposed. The hybrid PBC control strategy includes an outer loop active disturbance rejection (ADR)‐PI controller and inner loop PBC controller, providing a simple overall control structure and strong anti‐interference ability. Additionally, a space vector pulse‐width modulation (SVPWM) algorithm has been briefly introduced and applied to further improve the recovery and balance speed of the DC‐side capacitor voltages. Simulation and experiment results have validated the feasibility and effectiveness of the proposed hybrid PBC strategy and the SVPWM algorithm. In order to improve the large‐scale stability and dynamic performance of the novel unidirectional five‐level rectifier, a hybrid PBC control strategy and an SVPWM algorithm are proposed.